Relationship between glenohumeral horizontal abduction angle and scapular internal rotation angle at maximum shoulder external rotation during baseball pitching - Yuki Nomura, PhD, PT; Hajime Toda, PhD, PT, JSPO-AT; Masaki Katayose, PhD, PT, JSPO-AT; Shun Watanabe, MSc; Masahiro Yoshida, PhD, PT, JSPO-AT; Makoto Yoshida, PhD, PT, JSPO-AT; Keizo Yamamoto, PhD (JSES International)
Background: Increased scapulothoracic (ST) internal rotation at maximum external rotation (MER) during baseball pitching can decrease glenohumeral (GH) horizontal adduction, leading to excessive GH horizontal abduction. However, few studies have examined this direct relationship, and none have investigated the ST internal rotation angle at stride foot contact (FC) and MER. This study investigated the relationships between GH horizontal adduction and ST internal rotation angles at MER and between ST internal rotation angles at FC and MER. Methods: We recruited 15 asymptomatic collegiate baseball pitchers and assessed the ST internal rotation angle at FC and MER and GH horizontal adduction angle at MER during pitching using an optical motion tracking system. Pearson’s correlation coefficients determined the relationships between GH horizontal adduction and ST internal rotation angles at MER and between ST internal rotation angles at FC and MER. Results: The GH horizontal adduction angle at MER was significantly related to the ST internal rotation angle at MER (r = −0.58, P = .022). The ST internal rotation angle at FC was significantly related to the ST internal rotation angle at MER (r = 0.53, P = .045). Conclusions: The GH horizontal adduction angle at MER is associated with the ST internal rotation angle at MER in asymptomatic collegiate baseball pitchers, and the ST internal rotation angle at FC is related to the ST internal rotation angle at MER. Thus, the scapula and humerus should be controlled from FC to MER during pitching to reduce internal impingement risk in asymptomatic baseball pitchers.